2021
DOI: 10.1158/1541-7786.mcr-21-0171
|View full text |Cite
|
Sign up to set email alerts
|

ADGRL4/ELTD1 Expression in Breast Cancer Cells Induces Vascular Normalization and Immune Suppression

Abstract: ELTD1/ADGRL4 expression is increased in the vasculature of a number of tumor types and this correlates with a good prognosis. Expression has also been reported in some tumor cells with high expression correlating with a good prognosis in hepatocellular carcinoma (HCC) and a poor prognosis in glioblastoma. Here we show that 35% of primary human breast tumors stain positively for ELTD1, with 9% having high expression that correlates with improved relapse-free survival. Using immunocompetent, syngeneic mouse brea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Previously known that PECAM1 , CALCR , ADGRL4 , and CD93 genes are predominantly expressed in endothelial cells and regulate angiogenesis in tumor cells. 38 In addition, TME-regulation associated primarily consisted of genes mixture of endothelial-associated and stroma-associated topics with enrichment of distinct genes known to control tumor growth and promote stemness of cancer cells in microenvironment such as KCNN4 , IL6ST , and CD1B . 39 Furthermore, we observed a significant overlap between the gene-gene interactions derived from the interaction topic model and the gene network in the STRING database.…”
Section: Resultsmentioning
confidence: 99%
“…Previously known that PECAM1 , CALCR , ADGRL4 , and CD93 genes are predominantly expressed in endothelial cells and regulate angiogenesis in tumor cells. 38 In addition, TME-regulation associated primarily consisted of genes mixture of endothelial-associated and stroma-associated topics with enrichment of distinct genes known to control tumor growth and promote stemness of cancer cells in microenvironment such as KCNN4 , IL6ST , and CD1B . 39 Furthermore, we observed a significant overlap between the gene-gene interactions derived from the interaction topic model and the gene network in the STRING database.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, genes enriched in the endothelial topic recapitulate interactions of cancer cells in developing tumour vascular networks, especially in conjunction with endothelial cells. Previously known that PECAM1, CALCR, ADGRL4 , and CD93 genes are predominantly expressed in endothelial cells and regulate angiogenesis in tumour cells [Sheldon et al, 2021]. Additionally, TME-regulation associated topic primarily consisted of genes mixture of endothelial-associated and stroma-associated topics with enrichment of distinct genes known to control tumour growth and promote stemness of cancer cells in microenvironment such as KCNN4, IL6ST , and CD1B [Fan et al, 2022].…”
Section: Resultsmentioning
confidence: 99%
“…Huang et al 31 showed that targeting ADGRL4/ ELTD1 restores vascular function and improves prognosis in gliomas. A mouse breast cancer model with recombinant ADGRL4/ELTD1 expression exhibits metastasis to lung, more tumorous tissues and larger tumor vascular size 32 . In metastatic renal cell cancer, patients with high ADGRL4/ELTD1 expression in the tumor vasculature respond better to sunitinib treatment 33 .…”
Section: Discussionmentioning
confidence: 99%